Detection of delayed dental development in hypodontia through dental age assessment using panoramic radiographs - Sukmasari, Susi (2015)

(untitled)
The estimation of age is required for treatment planning in dentistry, medical, forensic or legal fields. From numerous studies, the development of tooth was tied to chronological age (CA). Some authors had found that the development of permanent teeth in children with hypodontia was delayed when compared with a matched control group. The delay will affect to the treatment and the prognosis. Development of tooth can be detected from the initial mineralization of tooth bud intraosseous until the tooth occlude with the opposing tooth using panoramic radiograph. The analysis of development tooth expresses the dental age (DA). This literature review aim is to outline the dental development in hypodontia patient through dental age assessment methods using panoramic radiograph. A brief explanation about hypodontia and age estimation methods followed by review of numerous study regarding dental age assessment in hypodontia. In conclusion, there were numerous studies using panoramic radiograph stated that dental development of hypodontia patients was delayed.